Central retinal artery occlusion in a patient with ANCA-negative Churg-Strauss syndrome - Miyazaki M (Dove Medical Press, 2012)
Yuji Kumano,1 Noriko Yoshida,2 Satoru Fukuyama,3 Masanori Miyazaki,2 Hiroshi Enaida,2 Takaaki Matsui11Ohshima Hospital of Ophthalmology, Fukuoka, 2Department of Ophthalmology, 3Research Institute for Diseases of the Chest, Graduate School of Medical Sciences, Kyushu University, Fukuoka, JapanAbstract: Ocular involvement in Churg-Strauss syndrome is infrequent. We describe the case of a 54-year-old woman with eosinophilia and involvement of the respiratory tract, skin, and peripheral nervous system, fulfilling the American College of Rheumatology criteria for Churg-Strauss syndrome. The patient presented with acute, painless vision loss in her right eye. Central retinal artery occlusion (CRAO) without accompanying retinal vasculitis was diagnosed by angiographic findings and funduscopic findings of retinal whitening with a cherry-red spot. Although her antineutrophil cytoplasmic antibody (ANCA) status was negative, CRAO was thought to be an ocular manifestation of Churg-Strauss syndrome, and appropriate treatment was planned. She was treated with high-dose corticosteroids and anticoagulant therapy. Her macular edema improved, but visual recovery was poor. Specific therapy to alter inflammation, blood coagulation, and rheology reportedly plays an important role in ANCA-positive patients with Churg-Strauss syndrome who develop CRAO. Regardless of ANCA status, high-dose corticosteroids should be considered for CRAO in patients with Churg-Strauss syndrome, as discussed in this case.Keywords: CRAO, ANCA, Churg-Strauss syndrome